MSAAM: A Multiscale Adaptive Attention Module for IoT Malware Detection and Family Classification. (21st June 2022) - Wang, Changguang; Zhao, Ziqiu; Wang, Fangwei; Li, Qingru
Abstract : Nowadays, the attack and defense of malware have presented asymmetric characteristic threats, which has disrupted the pace of IoT research. Traditional detection and family classification methods based on feature extraction, as well as the classical machine learning algorithms, have been afflicted with the problems of high time consuming and unbalanced numbers of malware samples. This paper designs a universal and effective Multiscale Attention Adaptive Module called MSAAM that can combine local and global feature information. It can automatically adjust the arrangement and proportion of channel and spatial submodules by auxiliary classifiers according to actual tasks. The traditional CliqueNet uses a circular feedback structure to improve the DenseNet, optimizes the information flow in a deep network, enhances the utilization of its parameters, and uses a multiscale strategy to prevent a sharp increase of its parameters. As a result, it shows a good effect in the study of image classification. By replacing the attention module in the traditional CliqueNet with the designed MSAAM, we present a new method to process the produced gray-scale images converted from the malware and thus get better results in malware processing. The improved CliqueNet runs on the benchmark datasets of MalImg and Microsoft's BIG 2015 to verify our presented method. After validation on the experimental benchmark datasets, the detection accuracy reaches 99.8%, while the family classification accuracy reaches 99.2% and 98.2% on the above two datasets, respectively. The presented method can solve the problem of unbalanced samples in malware family classification and is also effective against obfuscation attacks.